Disentangling Value: Financing Needs, Firm Scope, and Divestitures - Nanda, Vikram; Narayanan, M.P. (Journal of Financial Intermediation, 1999)
This paper presents a rationale for divestiture consistent with one of the reasons frequently cited by divesting firms, namely, that the firm is undervalued and splitting the firm into its component businesses will make it easier for the market to value the components accurately. When firms are undervalued due to unobservability of divisional cash flows, they may resort to divestiture to raise capital while overvalued firms will use external equity. Diversification thus might result in costly future divestiture. Firms trade off this expected cost of diversification against the benefit of higher levels of cheaper internal capital in deciding the scope of the firm. Journal of Economic Literature Classification Numbers: D82, G34, L22.